2014
DOI: 10.1155/2014/498453
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Weighted Model Order Reduction Technique and Error Bounds for Discrete Time Systems

Abstract: Model reduction is a process of approximating higher order original models by comparatively lower order models with reasonable accuracy in order to provide ease in design, modeling and simulation for large complex systems. Generally, model reduction techniques approximate the higher order systems for whole frequency range. However, certain applications (like controller reduction) require frequency weighted approximation, which introduce the concept of using frequency weights in model reduction techniques. Limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…A similar realization dependent modification of [18] is presented in [19] to reduce the approximation error. Later, Imran et al [20] presented an improvement of [11] by considering a similar effect on the eigenvalues of symmetric matrices. Some recent developments on model reduction are appeared in [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar realization dependent modification of [18] is presented in [19] to reduce the approximation error. Later, Imran et al [20] presented an improvement of [11] by considering a similar effect on the eigenvalues of symmetric matrices. Some recent developments on model reduction are appeared in [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the transformation of the original system into a new realization is non-unique by including variations of both algorithms using an additional factorization. It is observed that both proposed algorithms and their variations give a lower approximation error than [9,[11][12][13]17,19,20]. The advantages of the proposed algorithms are as follows: (i) assuring the stability of reduced model in case of single-and double-sided weights; (ii) availability of easily computable error bound; and (iii) easily extendable to discrete-time systems.…”
Section: Introductionmentioning
confidence: 99%
“…The use of input-, output-, or both-sided frequency weighting is possible; however, guaranteed stable reduced-order models (ROMs) are only achieved in the single-sided case [9]. Several modifications in [9] to guarantee stability have been presented in the literature [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Model order reduction is an indispensable tool to generate simpler reduced model while sacrificing some accuracy [1]. The commonly used model order reduction approaches include Krylov-subspace projection method [2], balanced truncation method [3,4], modal truncation method [5] and numerical optimization methods [6].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the frequency-domain approximation performance, the existing techniques generally tried to minimize the approximate error over the entire frequency range. For many practical model order reduction problems, it has been pointed out that the requirement on the approximation accuracy over some prespecified frequency range is more important than that beyond the frequency range [3,4,9,10,[34][35][36]. Therefore, it is more appealing to further improve the approximation performance over the concerned frequency ranges meanwhile ignoring the approximation performance over the rest frequency parts.…”
Section: Introductionmentioning
confidence: 99%